The economic impact associated with stent retriever selection for the treatment of acute ischemic stroke: a cost-effectiveness analysis of MASTRO I data from a Chinese healthcare system perspective - Osama O Zaidat; Xinguang Yang; Waleed Brinjikji; Emilie Kottenmeier; Hendramoorthy Maheswaran; Thibaut Galvain; Patrick A Brouwer; Mahmood Mirza; Tommy Andersson (Becaris Publishing Limited, 2024)
Aim: The aim of this analysis was to assess the cost-effectiveness of the EmboTrap Revascularization Device compared with the Solitaire™ Revascularization Device and Trevo Retriever for the treatment of acute ischemic stroke (AIS) from the perspective of the Chinese healthcare system. Methods: According to MASTRO I, a recent living systematic literature review and meta-analysis, mechanical thrombectomy (MT) with EmboTrap in the treatment of AIS resulted in better functional outcomes compared with the use of Solitaire or Trevo. Based on the proportion of patients that achieved 90-day modified Rankin Scale (mRS) scores of 0-2, 3-5 and 6 reported in MASTRO I, a combined 90-day short-term decision tree and Markov model with a 10-year time horizon was used to compare the cost-effectiveness of the three devices. The primary outcome was the incremental cost-effectiveness ratio (ICER), representing the incremental cost (in 2022 Chinese Yuan [CNY]) per incremental quality-adjusted life-year (QALY). The ICERs were compared against willingness-to-pay (WTP) thresholds of 1, 1.5 and 3-times the 2022 national gross domestic product (GDP) per capita in China. Results: Treatment with EmboTrap resulted in total QALYs of 3.28 and total costs of 110,058 CNY per patient. Treatment with Trevo resulted in total QALYs of 3.05 and total costs of 116,941 CNY per patient. Treatment with Solitaire resulted in total QALYs of 2.81 and total costs of 99,090 CNY per patient. Trevo was dominated by EmboTrap as it was a more costly and less effective intervention. As such, Trevo was not cost-effective at any WTP threshold. Compared with Solitaire, EmboTrap was more effective and more costly, with an ICER of 23,615 CNY per QALY. This result suggests that EmboTrap is cost-effective when compared with Solitaire since the ICER was lower than all WTP thresholds assessed. Conclusion: EmboTrap dominated Trevo and is cost-effective for the treatment of patients with AIS compared with Solitaire when assessed from the perspective of the Chinese healthcare system and based on the devicelevel meta-analysis MASTRO I. Selecting a stent retriever (SR) that optimizes 90-day mRS score is an important consideration from both a clinical and healthcare payer perspective in China as it is associated with reduced long-term costs and increased quality of life.